Nanocurcuminand chitosan-Pluronic F127-based hydrogel for 3rd degree burn treatment - Tuan, Dinh Van; Pham Thi Ly Na; Dang Le Hang; Cao Van Du; Mach Thi Anh; Doan Nguyen Vu; Tran Le Bao Ha; Nguyen Dinh Trung; Tran Ngoc Quyen (Vietnam Journal of Science and Technology, 2018)
Burns is one of the popular accidents today and usually leaves serious physical and mental damage. For long time represent acute wounds, burns are evolution into chronic wounds, if inadequately managed. Up to now, there have been abundancy of natural and synthetic products for burn healing. In the study, we fabricated a thermosensitive nanocomposite hydrogel in which incorporated dual active curcumin and chitosan. Beside of a well-known characteristic of chitosan for wound healing, curcumin has been a lot of interest in burn wound healing application due to ability in depleting the action of oxidative radicals and stimulation of fibroblast cells. In order to enhance the therapeutic efficacy of curcumin, we introduced the new method to synthesize nanocurcumin in the a thermosensitive chitosan-g-Pluronic F127 copolymer solution under ultrasonication. The rheology of aqueous solutions of this material is studied as a function of temperature. The solutions of this material undergo a transition to a gel at higher temperature, above which a complex rheological behavior is observed. In addition, a minimum inhibitory concentration of this material was determined for a variety of bacterial and was compared to that of curcumin. It was found that the aqueous dispersion of this material was much more effective than curcumin against both positive and negative gram bacterial. In the third degree burn models, the nCur-CP hydrogel performed a higher burn healing rate as compared to Silvirin-treated burn. These data suggest that the nanocomposite hydrogel may be great potential for burn treatment